Preface - The Ancient Capitals in the Ararat Plain of Armenia : Conference in the Wine History Museum of Armenia 18 – 20 April 2023 in Ashtarak, Armenia - Gyulamiryan , Hayk; Lichtenberger , Achim; Muradyan , Syuzanna R.; Schreiber , Torben; Zardaryan , Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
From the 4th century BC to the 4th century AD, ‘Hellenistic’ Armenia had a total of six different capitals. Five of these were located on the Ararat plain. From Armavir (capital c. 330-210 BC) the capital was moved to Yervandashat-Yervandakert (capital c. 210-180 BC) and then to Artashat (capital c. 180-77 BC). After the expansion of the Armenian Kingdom under Tigranes the Great, the capital of Greater Armenia was briefly located outside the Ararat Plain, at Tigranakert (capital 77-69 BC), but was moved back to Artashat (again capital 69 BC – c. 120 AD). From here the capital was moved to Vagharshapat (capital c. 120-330 BC) and later to Dvin (336-428 BC).